Kontribusi Pajak Hotel Terhadap Pendapatan Asli Daerah (Suatu Studi Di Dinas Pendapatan Kota Manado) - Arifin, Fajriana; Rompas, Welson Yappi; Londa, Very (Sam Ratulangi University, 2015)
ABSTRACT : Local Taxes are one source of local revenue, which is expected to help defray for implementations the local autonomy, which is able to organize and manage own household well as revenue from the government in the form of subsidy / assistance. The sources of local tex are expected to be a source of financing local governance and development. Specialy of Manado City as a tourism place and business capable captured by tourism businesses are marked by the number of hotels built, well-star hotels or budget hotels. It can see by the growing and increasing of manado city may can showing that potential of hotel tax is the source of local that can be optimal.The method of this research : This research used the descriptive quatitative method that uses secondary data in the form of time series with the sample that hotel tax revenue in 2010 s / d 2014.The result of Researches : based in the target of hotel tax that fixed by the government of manado city. The hotel tax in manado city enough to contribute During the period of 2010 s / d in 2014 amounted to Rp. 66,946,272,913 ie annual average hotel tax provides sumbangsi at 7:58% to PAD Manado.That the hotels in Manado City Tax enough to contribute in the acceptance of the original local revenue.Keywords: Hotel Tax, Local Revenue.